(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and objectives: The most common gynecological malignancy in Kurdistan is ovarian cancer with high morbidity and mortality. Ovarian cancer patient usually diagnosed at late stage because they have non-specific symptom at early stages. Most ovarian cancer patient treated with surgical operation followed by adjuvant- chemotherapy. Methods: In this retrospective (cohort) study, a total 155 patient treated at Azadi cancer center in Duhok between May 2015 and April 2021. Clinico-pathological information data and case registration exanimated to assess the management outcome, stage of disease, histo- pathology of the tumor and overall -survival (OS) rate of patients. Results: the mean age was 48.5 years (range 12-89 years). The most common histology subtype was epithelial ovarian cancer. In this study patient with late stage disease were more common than early stage ovarian cancer patient, 56% and 44% respectively. Median OS of all patient included in this study is 28 months (95% CI of 24-34 months). Patients with early stage disease (stage I and stage II) and had better outcome to patient with advance stage disease (stage III and IV) (P=0.006). Patients treated with upfront surgery after diagnosis had uppermost OS with a median overall survival, 31 months (95% confidence interval of 27-39 months) compared to patient treated with neoadjuvant treatment or first line treatment with OS 21 months (95% confidence interval of 12-30 months) and 5 months (95% confidence interval of 1-31 months) respectively (P= 0.0137). Conclusions: Ovarian cancer has an improved prognosis when diagnosed at early stages. Surgery is the main stay of the treatment, followed by proper chemotherapy.